Automate your busywork : do less, achieve more, and save your brain for the big stuff - Tank, Aytekin (Hoboken, New Jersey : John Wiley & Sons, Inc., 2023)
"Most people don't work with time, they work against time. But how you spend your time is everything. This book is not about how to do XXX number of things within X hours or about turning you into a productivity machine. This book is about time well spent. This book is about protecting and mastering your most precious asset, from an entrepreneur who built a company to 10 million users with no outside funding. Automate Your Busy Work requires you to explore why you are doing busywork in the first place. The book takes you from busy work to less work, to the best use of your time"--
Includes bibliographical references and index.
Keywords: Time management